Presidential Threshold in Indonesian Election: An Islamic Law Perspective - Sholahuddin Al-Fatih; Fitria Esfandiari (Fakultas Hukum Universitas Islam Malang, 2022)
Direct presidential election every five years is the embodiment of democracy in Indonesia. The issue of thresholds as a condition for nominating candidates for president and vice president has always not found a solution. Changes in the threshold which was initially 10% then the number changed to 20% until now. This study aims, among others, to evaluate disharmony in the process of determining the threshold. The approach method used is normative juridical, through literature study using primary and secondary legal materials. The results of this study conclude that the reconstruction of the presidential election threshold based on the perspective of Islamic law is very much needed because it is very vulnerable to friction and tug-of-war between political parties.